2015
DOI: 10.1515/biolog-2015-0085
|View full text |Cite
|
Sign up to set email alerts
|

Brassinosteroids roles and applications: an up-date

Abstract: Brassinosteroids are plant steroidal compounds involved in many functions related with plant development, metabolism, signalling and defense against a wide range of biotic and abiotic stresses. Plant architecture, which has a major effect on crop yield, is strongly influenced by brassinosteroids action. Brassinosteroids are recognized as key regulators of plant growth and development involved in a broad spectrum of processes at the molecular, cellular, and physiological levels. These roles suggest that many of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 60 publications
1
22
0
Order By: Relevance
“…Brassinosteroids (BRs) are plant steroid hormones, which play essential roles in plant growth and development 1 2 , and also confer tolerance to a wide range of abiotic stresses 3 4 . The BR signalling pathway is one of the best-understood signal transduction pathways in the plant hormone field.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Brassinosteroids (BRs) are plant steroid hormones, which play essential roles in plant growth and development 1 2 , and also confer tolerance to a wide range of abiotic stresses 3 4 . The BR signalling pathway is one of the best-understood signal transduction pathways in the plant hormone field.…”
mentioning
confidence: 99%
“…BR activated signalling by BRI1 inactivates the negative regulator BRASSINOSTEROID INSENSITIVE2 (BIN2), which in turn leads to activation of two closely related transcription factors BRI1-EMS SUPPRESSOR1 (BES1) and BRASSINAZOLE-RESISTANT1 (BZR1) and expression of an array of BR-regulated genes 5 6 . BAK1 and its homologs are also a required component of pathogen/microbe-associated molecular patterns (PAMPs/MAMPs)-triggered immunity and Mi-1-mediated resistance to insect herbivores 1 2 .…”
mentioning
confidence: 99%
“…Owing to its multiple effects, it can be used in horticulture to improve growth, yield and quality. In recent, this hormone was proved as a natural, nontoxic, and safe to environment, thus it may be used in horticultural crops to improve the quality of the produce [73]. There is several evidence that it acts as growth promoter in plants either solely or in combination with other hormones like GA3, jasmonic acid and polyamines.…”
Section: Brassinosteroidsmentioning
confidence: 99%
“…4). Brassinosteroids are the most important naturally occurring plant growth-promoting steroidal hormones which not only play a pivotal role in inducing the disease resistance or plant innate immunity but also regulates several growth and development processes like photo-morphogenesis, hormonal regulation, dwarfism, seed germination, change in the distribution pattern of stomata, flowering, senescence, pollen tube elongation, male sterility, xylem differentiation and root growth, confer tolerance/resistance to a broad range of biotic and abiotic stresses (thermal, salinity, oxidative, heavy metal stresses) in several plant species (Krishna, 2003;Kagale et al, 2007;Bajguzand Hayat, 2009;Divi and Krishna, 2010;Coll, et al, 2015).We observed that number of brassinosteroids synthesis genes in healthy (HB-1) and malformed buds (MB-1) were similar. In malformed tissues, the biosynthesis genes increased as the stage of malformation proceeds from MB-1 to MB-3; whereas in healthy tissues, from bud to panicle development stage, it remained unchanged.…”
Section: Target Genes Of Brassinosteroids Signalingmentioning
confidence: 99%